Construction and analysis of an aberrant lncRNA-miRNA-mRNA network associated with papillary thyroid cancer. Issue 45 (6th November 2020) - Jiang, Yanxia; Wang, Jiao; Chen, Jian; Wang, Jiancheng; Xu, Jixiong
Abstract : Abstract: Accumulating evidence has indicated that long noncoding RNAs (lncRNAs) are the main constituents of competing endogenous RNA (ceRNA) networks. Nonetheless, in the lncRNA-related ceRNA network of papillary thyroid cancer (PTC), the function of cancer-specific lncRNAs, as well as their use for the potential prediction of PTC prognosis, remains unclear. In this study, 384 RNA sequencing (RNA-seq) profiles of PTC patients were attained from The Cancer Genome Atlas (TCGA), an open-source database that offers vast amounts of RNA-seq data, and 75 miRNAs, 495 lncRNAs, and 1099 mRNAs ( P < .05 and |logFC| >2) were detected when compared with normal tissues. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways were analyzed using the Cytoscape plug-in BinGo. An aberrant lncRNA-mRNA-miRNA ceRNA network consisting of 31 differentially expressed (DE)-lncRNAs, 13 DE-miRNAs, and 134 DE-mRNAs was built in TCGA. On the basis of overall survival (OS) analysis, 6 lncRNAs ( CCAT1, SYNPR, SFTA1P, HOTAIR, HCG22, and CLDN10 ) were identified as prognostic biomarkers for patients in TCGA ( P < .05). Through qRT-PCR, we designated 6 cancer-specific lncRNAs as having great significance for survival by verifying their expression in the 60 PTC patients who were diagnosed. The qRT-PCR and TCGA results were completely consistent. Our research provides data for further understanding the lncRNA-miRNA-mRNA ceRNA network and elucidating the molecular mechanisms of PTC. Abstract : Supplemental Digital Content is available in the text